2020
DOI: 10.3390/pr8091190
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Pyrolysis of Biomass Waste: A Mini Review

Abstract: The utilization of biomass waste as a raw material for renewable energy is a global concern. Pyrolysis is one of the thermal treatments for biomass wastes that results in the production of liquid, solid and gaseous products. Unfortunately, the complex structure of the biomass materials matrix needs elevated heating to convert these materials into useful products. Microwave heating is a promising alternative to conventional heating approaches. Recently, it has been widely used in pyrolysis due to easy operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 94 publications
(111 reference statements)
1
50
0
1
Order By: Relevance
“…Microwave-assisted hydrothermal treatment (MA-HTT) can also be used for the production of value-added chemicals and biomaterials. 130 As described above, the use of microwave heating to achieve hydrothermal conditions has several advantages over conventional heating, primarily including time and energy savings and higher products yields. 80,128 During the MA-HTT, biomass decomposes into valuable water-soluble compounds, which can be used in a plethora of applications.…”
Section: Microwave-assisted Hydrothermal Treatment (Ma-htt) For the Production Of Renewable Valueadded Chemicals And Biomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microwave-assisted hydrothermal treatment (MA-HTT) can also be used for the production of value-added chemicals and biomaterials. 130 As described above, the use of microwave heating to achieve hydrothermal conditions has several advantages over conventional heating, primarily including time and energy savings and higher products yields. 80,128 During the MA-HTT, biomass decomposes into valuable water-soluble compounds, which can be used in a plethora of applications.…”
Section: Microwave-assisted Hydrothermal Treatment (Ma-htt) For the Production Of Renewable Valueadded Chemicals And Biomaterialsmentioning
confidence: 99%
“…An increase in microwave power produces higher power densities, increasing production rates and diminishing associated energy production costs. 130 Thangavelu et al 138 found that the highest glucose yield (43.8%) was obtained with high microwave power (900 W) during the MA-HTT of sago pith using carbon dioxide as a catalyst. In another study, these authors also proved that an increase in the microwave power exerted a positive effect on the glucose yield using H 2 SO 4 ; however, when HCl was used as a catalyst, the microwave power had a negligible effect.…”
Section: Other Factors: Solid/water Ratio and Microwave Powermentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11,12 ] Conventional pretreatment methods are classified into biological (e.g., fungal and bacterial pretreatment), physical (e.g., milling, ultrasonic, microwave, mechanical extrusion); chemical (e.g., acid hydrolysis, alkaline hydrolysis, organosolv, oxidation delignification, ozonolysis), physicochemical pre‐treatment (e.g., steam explosion, ammonia fiber explosion) methods. [ 11–14 ] Emerging technologies are developed based on the use of ionic liquids (ILs), [ 15 ] deep eutectic solvents (DES), [ 16 ] microwave‐assisted methods, [ 17 ] sub/supercritical fluids (SCFs), [ 18,19 ] aiming at enhancing the recyclability of solvents/reagents of pretreatment processes. [ 15,20–22 ] These advanced solvents are recyclable and have high selectivity for removing noncellulosic fractions of the LC biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Khelfa et al (2020) reported that microwave-assisted pyrolysis of pinewood sawdust mixed with activated carbon improved biomass heating, reduced energy consumption, and coproduct quality after the treatment. Also, Ethaib et al (2020) reported that microwave absorbers could adjust product distribution, improve bio-oil, biochar, and bio-gas at different treatment conditions, including the energy efficiency of the process. Biochar is a solid material produced from the thermochemical decomposition or carbonization of biomass.…”
Section: Introductionmentioning
confidence: 99%